Ganfule capsule alleviates bile duct ligation-induced liver fibrosis in mice by inhibiting glutamine metabolism - Ke, Chang; Gao, Jianlong; Tu, Jiyuan; Wang, Yan; Xiao, Yangxin; Wu, Yuan; Liu, Yanju; Zhou, Zhongshi (Frontiers in Pharmacology, 2022)
Abstract: Background: Liver fibrosis is a pathological outcome of a variety of liver diseases and it can also progress into liver cirrhosis and liver cancer. Specific liver antifibrotic drugs have not been yet clinically approved. Studies have demonstrated the protective effects of Ganfule capsule (GFL) on the liver and its therapeutic potential in hepatic cancer. However, the mechanism of GFL is not clear in the treatment of liver fibrosis. Objective: To study the protective effect of GFL on liver fibrosis and its possible mechanism. Methods: The cholestatic liver fibrosis model was prepared by subjecting C57BL/6 mice to bile duct ligation (BDL). The GFL groups were treated with different concentrations of GFL for 14 days. Pathological analysis, serum biochemical index detection, metabonomic analysis, immunohistochemistry, Western blot, and real-time PCR were carried out. Results: GFL could alleviate the liver injury and liver fibrosis caused by BDL in mice. Metabonomic analysis of mice serum showed postoperative metabolic disorder which could be alleviated by GFL through glutamine metabolism; valine, leucine and isoleucine biosynthesis ; aminoacyl tRNA biosynthesis and other metabolic pathways. GFL affected glutamine metabolism by inhibiting the activity of glutaminase 1 (GLS1). The activation of GLS1 is regulated by the NF-κB pathway and experiments showed that GFL could inhibit IκB-α and NF-κB p65 phosphorylation. Conclusion: This study confirms the protective effect of GFL on liver injury and shows that GFL affects glutamine metabolism by inhibiting the NF-κB pathway and eventually alleviates liver fibrosis. These results are conducive to the development of new therapeutic drugs for liver fibrosis.